GENERAL GEOLOGY OF POS BROOKE ALONG JALAN GUA MUSANG-CAMERON HIGHLANDS WITH EMPHASIS ON TECTONIC EVOLUTION - LEE, YIN YIN (Universiti Teknologi PETRONAS, 2014)
The transect along Jalan Cameron Highlands-Gua Musang cuts across the Bentong-Raub suture. The main lithology found at the area consist of amphibolite schist, hornfelsic amphibolite schist, cataclasite and granite. Olistostromes can also be found at the area. Based on the structural analysis, the maximum stress is coming from the NE-SW direction. There are three main tectonic events that lead to the formation of the structures found at the area of study namely a compression regime caused by the subduction of Sibumasu and Indochina, an extensional regime caused by the Indosinian Orogeny in the Late Triassic and finally the extrusion tectonics caused by the docking of India into Asia forms the strike slip faults and caused the reactivation of the faults causing another set of normal faults to be formed.